Only 4.9% (24/494) of original papers on migraine and headache published in Cephalalgia 2014–2018 concerned actual spontaneous or provoked migraine/headache attacks: A comment. (26th November 2019) - Tfelt-Hansen, Peer
The aim was to evaluate whether headache experts rarely, if ever, investigate spontaneous or provoked migraine/headache attacks. All the 494 Original Articles in five volumes of Cephalalgia (from 2014 to 2018) were screened and classified as dealing with spontaneous or provoked migraine/headache attacks, or other aspects of migraine/headache. Only 4.9% (24/494) of papers reported on studies of spontaneous and provoked migraine/headache attacks. Investigations of the pathophysiology of spontaneous or provoked migraine/headache attacks in humans could result in the development of better drugs for migraine, and to the identifications of biomarkers for use in personalized medicine.